Systematic approach for uncertainty delta E data for composites panel coating analysis - Abu Bakar, E. (Pleiades Publishing, 2018)
In general, Aerospace industry has been developing significantly throughout the economy as demands on technology in advanced transportation is increasing. Furthermore, as a multi-billion dollar industry, the efforts is needed to sustain high quality of products for safety, minimizing waste during process and increase in a pace of manufacturing. Therefore, Six Sigma tool which is DMAIC approach is chosen to presents a case of an efficient and systematic method of improvement cycle âDefine, Measure, Analyze, Improve and Controlâ to define and analysis defect, hence to improve the quality of production in aerospace industry. In this study, the focus is done by studying how the implementation of Six Sigma on an aerospace company especially to solve the problem of uncertainty condition of Delta-E for Panel Coating. By using the DMAIC approaches, defects and problems that arise in the production line of the company are being sorted out and solved. Trials and experiments were also conducted on the companyâs production line and the data is being collected for analysis and study purpose. Through observation and data taken from above problem, analyzed results perform remarkable solution to be applied by Aerospace Industry. Â© 2018, Springer Nature Singapore Pte Ltd.